Distributed wireless power and data transmission for a network of neural nodes in the brain - Putra, Nicholas Kenneth Naga (Nanyang Technological University, 2022)
Wireless Power Transmission has been applied in various devices due to its benefits. This research project specifically focuses on engineering a Brain Machine Interface (BMI) device on maximizing its power transfer. This paper focuses on further increasing the efficiency on such devices.